A cost-effective self-biased magnetoelectric effect in SrFe12O19/Metglas/Pb(Zr, Ti)O3 laminates. (12th September 2016) - Ma, J N; Xin, C Z; Ma, J; Lin, Y H; Nan, C W
Abstract: By introducing the hard magnetic SrFe12 O19 ribbon, a self-biased magnetoelectric laminate—SrFe12 O19 /Metgals/Pb(Zr, Ti)O3 was successfully designed. Without any external magnetic field, the laminates exhibit giant self-biased ME responses of 1 V (cm Oe) −1 at quasi-static condition, and up to 29 V (cm Oe) −1 at high-frequency resonance. The induced ME voltage shows a good linear relationship to the applied ac magnetic field with amplitude as low as 10 −8 T at 1 kHz, and the self-biased ME property presents an outstanding stability in a time span of 12 months.